1989
DOI: 10.1042/bj2580473
|View full text |Cite
|
Sign up to set email alerts
|

pH effects on the haem iron co-ordination state in the nitric oxide and deoxy derivatives of ferrous horseradish peroxidase and cytochrome c peroxidase

Abstract: The spectral (e.p.r. and absorbance) properties of the NO and deoxy derivatives of ferrous horseradish peroxidase (HRP; EC 1.11.1.7) and baker's-yeast cytochrome c peroxidase (CCP; EC 1.11.1.5) were investigated between pH 7 and pH 2; over the same pH range the kinetics for CO binding were also determined. At neutral pH the e.p.r. and absorption spectra of the NO and deoxy derivatives of HRP and CCP are typical of systems in which the haem iron is in the hexaco-ordinated state and the pentaco-ordinated state r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…1 and 2). There were several factors to facilitate the cleavage of the iron-histidine bond, including a repulsive trans effect of NO (27,61) and the protonation of the proximal histidine residue (62,63). The latter was proposed for the proximal histidine release of myoglobin and peroxidases at acidic pH.…”
Section: Fig 2 No Binding Analyses By a Stopped Flow Methodmentioning
confidence: 99%
“…1 and 2). There were several factors to facilitate the cleavage of the iron-histidine bond, including a repulsive trans effect of NO (27,61) and the protonation of the proximal histidine residue (62,63). The latter was proposed for the proximal histidine release of myoglobin and peroxidases at acidic pH.…”
Section: Fig 2 No Binding Analyses By a Stopped Flow Methodmentioning
confidence: 99%
“…Similar results were found when using either SNAP as NO donor or TMB as substrate. These results may easily be explained if we take into consideration that NO binds to the inactive ferrous form of peroxidases (Ascenzi et al 1989), thus withdrawing activated enzyme forms from the catalytic cycle. In addition, we cannot discard a possible direct chemical action of NO in scavenging of the free radicals generated during peroxidase action, which would explain the minor differences found between the two substrates.…”
Section: Effect Of No-releasing Compounds On the Catalytic Activity Omentioning
confidence: 99%
“…In addition, the properties of the iron-histidine bond may be monitored, since the ironhistidine stretching mode is present in five-coordinate ferrous hemes (10,11). The previous optical absorption experiments on heme proteins at low pH were done with stopped-flow techniques because most of the proteins are not stable for a long period of time under these conditions (3)(4)(5)(6). It is difficult to measure the resonance Raman spectrum with a stoppedflow apparatus because irradiation of a fixed sample with a laser can give photochemical effects such as ligand dissociation (11) and photoreduction (12).…”
mentioning
confidence: 99%
“…Myoglobin (Mb) is one of the simplest heme proteins and has been extensively studied in order to understand the factors that control the binding and release of oxygen, its physiological ligand, as well as CO, which is a convenient oxygen substitute for laboratory studies (1,2). In several reports, the binding of CO to Mb (3,4) and other heme proteins (5,6) has been monitored after a rapid drop in pH. For most Mbs and monomeric hemoglobins (Hbs) (3,4) and for human tetrameric Hb (5), it was found that at low pH (-2.5) a large increase in the CO-binding rate occurs.…”
mentioning
confidence: 99%